Conflict of real and digital personality in media communication: Results of the study - A. K. Mamedov; O. V. Smirnova; G. V. Denissova; O. V. Sapunova (RUDN journal of Sociology, 2025)
The article considers the discrepancy between digital personality created by an individual in the media space and one’s real image. The conducted exploratory study was intended to confirm the presence and/or absence of the intention of media communication participants to form a simulacrum which acts as a virtual mask replacing and even modifying real personality. The authors focus on identifying a statistically significant tendency towards cognitive dissonance of social network users as determined by the contradiction between their real and digital images. The methods of formalized survey and unfinished sentences were used, providing opportunities for self-analysis in the digital space. The evaluated key parameters were the following aspects of media communication: anonymity vs explicit position; conformity, desire to receive social approval vs defending one’s position; following fashion vs following one’s interests; tendency towards realistic self-presentation vs preference for idealized self-presentation. The sample consisted of 112 respondents aged 19 to 32 - students and postgraduates of Russian higher education institutions. The empirical results proved respondents’ desire to explicitly express their own point of view and non-conformity and disloyalty to popular/widespread opinions. Self-analysis of users’ behavior in social networks revealed the dominance of realistic self-presentation, the desire to form a positive virtual image with special attention to its visual component, and a significant coincidence of virtual and real images.